JURIDICAL ANALYSIS OF STATE SOVEREIGNTY IN THE CONTEXT OF KOLAKA INDUSTRIAL DEVELOPMENT IN SOUTHEAST SULAWESI - Mufrina; Roestamy, Martin (DE'RECHTSSTAAT, 2024)
Although there are clear regulations regarding state control rights, implementation in practice often faces complex challenges. The main challenges include conflicts with local communities who have traditional rights related to land and natural resources around industrial areas. This study aims to conduct a legal analysis of the implementation of state control rights in the context of industrial development in the Kolaka Industrial Area, Southeast Sulawesi. The normative research method is a review of legal regulations governing natural resource management, industrial licensing, and environmental protection. With a literature study approach to collect data from various legal sources and related literature. The results of the study show that the implementation of state control rights in practice faces complex challenges, including conflicts with local communities who have traditional rights related to land and natural resources. Community participation in the decision-making process is key to avoiding social conflict and ensuring the sustainability of industrial projects. The conclusion of this study underlines the importance of wise and transparent management by the government in implementing state control rights, so that it can integrate national, social, and environmental interests in a balanced manner in industrial development in Southeast Sulawesi.